WEAKENING THE OPPORTUNITIES OF NATION-STATES TO FORM AN INDEPENDENT ECONOMIC POLICY - KALINICHENKO, Zoia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the process of forming an independent and effective economic policy of the state in the conditions of global development. The priority tasks and features of the formation of the state in the conditions of international competition of its own national economic system are determined. Proposed criteria for determining the level of independence of the state’s economic policy. The reasons for the loss of economic independence of the states in the era of globalism and the main advantages of a strong economy for the development of the state’s own development strategy are investigated. The main factors of the impact of globalization on the loss of relative economic independence by individual countries are systematized. The main signs of economic independence of the state are highlighted and the consequences of negative trends leading to the loss of independence are determined. The role of institutions in formulating strategic priorities of economic policy and state development programs is emphasized. Uncertainty and change are associated with the need to develop and implement an effective national strategy. Economic development is achieved precisely in the conditions of growing interdependence of the national and world economy. State economic policy should proactively take into account the consequences of a possible loss of economic independence in the context of globalization and ensure positive growth trends for the national economy.